2022
DOI: 10.1038/s41387-022-00185-4
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of gestational diabetes shows dysregulated lipid metabolism post-weaning, after return to euglycaemia

Abstract: Background Gestational diabetes is associated with increased risk of type 2 diabetes mellitus and cardiovascular disease for the mother in the decade after delivery. However, the molecular mechanisms that drive these effects are unknown. Recent studies in humans have shown that lipid metabolism is dysregulated before diagnosis of and during gestational diabetes and we have shown previously that lipid metabolism is also altered in obese female mice before, during and after pregnancy. These obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…The analysis of the present study used only MS data and was similar to previous studies (Furse et al, 2021b , 2022 ) but with adjustments for four rather than two groups. The tissues used were mapped to the known biological/metabolic network (Fig.…”
Section: Methodsmentioning
confidence: 94%
“…The analysis of the present study used only MS data and was similar to previous studies (Furse et al, 2021b , 2022 ) but with adjustments for four rather than two groups. The tissues used were mapped to the known biological/metabolic network (Fig.…”
Section: Methodsmentioning
confidence: 94%
“…Lipid Traffic Analysis v2.3 was used for this study (Furse et al, 2021a ; 2022a , b ). The code was executed in RStudio(v1.2.5x).…”
Section: Methodsmentioning
confidence: 99%
“…The shorter onset time of GDM means it has been easier to research and subsequently its molecular origins have received a good deal of attention. Research into the lipid metabolism around GDM has shown that lipid metabolism is disrupted in humans at least 10 weeks before diagnosis of hyperglycaemia (Furse et al, 2019 ; Lu et al, 2016 ), that the lipid composition of maternal blood plasma is different before, during and after the onset of GDM (Furse et al, 2021a ) and that dysregulated lipid metabolism persists throughout the maternal system after weaning (Furse et al, 2022a ). This evidence strongly suggests that dysregulated lipid metabolism has a role in the pathophysiology of GDM, raising questions about a possible role for dysregulated lipid metabolism in T2DM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the present study used only MS data and was similar to previous studies (Furse et al, 2021b(Furse et al, , 2022 but with adjustments for four rather than two groups. The tissues used were mapped to the known biological/metabolic network (Fig.…”
Section: Lipid Traffic Analysismentioning
confidence: 98%